THU0531 A PROSPECTIVE STUDY EVALUATING THE ROLE OF 68GA-RGD2 PET/CT ANGIOGENESIS IMAGING IN ASSESSING DISEASE ACTIVITY AND TREATMENT RESPONSE IN RHEUMATOID ARTHRITIS AND ITS COMPARISON WITH DAS28. (2nd June 2020) - Kavanal, A. J.; Bhattacharya, A.; Sharma, A.; Shukla, J.; Chattopadhyay, A.; Vatsa, R.; Rana, N.; Kaur, G.; Mittal, B. R.
Abstract : Background: PET/CT imaging of synovial angiogenesis using 68 Ga-RGD (cyclic tripeptide agent targeting αv β3 integrin) to study disease activity in rheumatoid arthritis (RA) has been demonstrated earlier in a few patients. However, post treatment changes in disease activity on 68 Ga-RGD2 PET/CT imaging have not been adequately assessed. Objectives: To compare the performance of 68 Ga-RGD2 PET/CT with disease activity score (DAS) 28 in assessing disease activity and treatment response in RA. Methods: Thirty patients (24F, 6M) aged 43±12 years with clinically diagnosed RA were prospectively studied. After calculation of DAS28 by a rheumatologist, all 30 patients underwent 68 Ga-RGD2 PET/CT scan. Of these, 27 patients underwent a second 68 Ga-RGD2 PET/CT scan and clinical assessment after at least 3 months of treatment. Total body and regional images of the upper limbs were acquired and interpreted by two nuclear medicine physicians blinded to the clinical findings. Joints showing focally increased tracer uptake compared to the background were considered positive and joints showing uptake equal to or less than background were considered negative. Data of 30 patients were used for inter-observer and inter-modality agreement calculations. Changes in PET parameters and DAS28 were compared in 27 patients to assess treatment response. Results: Out of 1560 joints examined in the initial scan, 394 were positive on PET/CT compared to 348 on clinical evaluation. Inter-observer agreement between nuclear medicine physicians was excellent (Cohen's kappa 0.92, p<0.05) and inter-modality agreement between PET and clinical examination was moderate (Cohen's kappa 0.55, p<0.05). The DAS28 and SUVmax values (highest and average) of 27 patients showed significant reduction on follow-up compared to the initial evaluation. There was significant correlation between percentage change in DAS28 and percentage change in scan parameters like PET positive joint counts (0.689, p<0.001), average SUVmax (0.712, p<0.001) and highest SUVmax values (0.558, p=0.003) of scan-positive joints in 27 patients. Additional advantages of 68 Ga-RGD2 PET/CT included objective assessment, whole body evaluation of all small and large joints, and greater reproducibility. Conclusion: 68 Ga-RGD2 PET/CT is a promising tool for objective assessment of disease activity and treatment response in patients with RA. Acknowledgments: This study was supported by Indian Council of Medical Research, New Delhi [grant no.3/2/June-2017/PG-Thesis-HRD (23)] Disclosure of Interests: None declared